2011
DOI: 10.1128/aac.00562-11
|View full text |Cite
|
Sign up to set email alerts
|

Nonconcordance with Surgical Site Infection Prevention Guidelines and Rates of Surgical Site Infections for General Surgical, Neurological, and Orthopedic Procedures

Abstract: Surgical site infection (SSI) is a common and preventable complication of surgery, but the relative importance of individual measures recommended by guidelines has not been determined. Elective general surgical, neurological, and orthopedic procedures requiring antibiotic prophylaxis from a 3-month period were retrospectively studied to determine concordance with SSI prevention guidelines and to identify factors which predicted the development of SSIs. A total of 216 surgeries were reviewed, with 18 SSIs (8.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
4
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 33 publications
4
36
4
5
Order By: Relevance
“…The SSI rate per patient observed in our study was similar to a previous local study [27]; but higher than the overall SSI rate reported by others (1.2%-8.3%) [19,25,28,29] except for India (20.1%) [30]. The reason for this is uncertain but the impact of a high prevalence of inappropriate antibiotic use for prophylaxis, current infection control policies or a combination of these factors requires further consideration.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The SSI rate per patient observed in our study was similar to a previous local study [27]; but higher than the overall SSI rate reported by others (1.2%-8.3%) [19,25,28,29] except for India (20.1%) [30]. The reason for this is uncertain but the impact of a high prevalence of inappropriate antibiotic use for prophylaxis, current infection control policies or a combination of these factors requires further consideration.…”
Section: Discussionsupporting
confidence: 81%
“…Contrary to this, many developed countries prefer the use of first generation cephalosporins or a combination of penicillin and betalactamase-inhibitors [18,20,23,24,25]. Studies, however, have shown no difference between the use of broad spectrum and narrow spectrum prophylactic antibiotics in terms of lowering rate of SSI [12].…”
Section: Discussionmentioning
confidence: 99%
“…12 In January 2011, the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) 13(p517) published a treatment guideline for pediatric tonsillectomy that included a recommendation that "clinicians should not routinely administer or prescribe perioperative antibiotics to children undergoing tonsillectomy." Because adherence to national prescribing guidelines has been shown to vary 14,15 we examined the effect of this guideline on antibiotic use with tonsillectomy and measures of postoperative morbidity across a large, pediatric health care network.…”
mentioning
confidence: 99%
“…Die Umsetzung dieser Maßnahmen hat einen signifikanten Einfluss auf die Rate nosokomialer Infektionen [3,21,22]. …”
Section: Präventionsmaßnahmenunclassified